Monographic revision of the endemic Helix mazzullii De Cristofori & Jan, 1832 complex from Sicily and re-introduction of the genus Erctella Monterosato, 1894 (Pulmonata, Stylommatophora, Helicidae) Zootaxa, 3134, 1–42 (Erratum) - Colomba, - (Zootaxa, 2012)
Erratum